PENGARUH RETURN ON INVESMENT, RELEVANSI NILAI, KETEPATAN WAKTU TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2008 – 2012 - -, Immu Puteri Sari (MENARA EKONOMI, 2015)
This Research aims to examine and obtain empirical evidence of the effect of the Return On Investment, relevance and timeliness of the value of the stock price at the manufacturing companies listed in Indonesia Stock Exchange period 2008 - 2012. Variables tested in this study is the stock price, ROI, Relevance and Timeliness value. Data collection techniques in this study with technical documentation. The sample of this study using the 106 companies included in the list IDX row from 2008-2012 which were taken by using purposive sampling method. In this study the data that will be used is secondary data obtained from the web site IDX www.idx.co.id  and other data. Data analysis method used is multiple regression analysis techniques. The results of this study indicate that the ROI, relevance and timeliness of the value of an effect on stock prices simultaneously with the results of the analysis show the adjusted R2 value of 0.279 or 27.9%. In this study the variables that significantly influence the stock price is the ROI, it is indicates that when a company's ability to generate increased profits, the stock price will rise. while the variable that does not have a significant effect on stock prices that value relevance and timeliness. This indicates that when the value relevance of accounting information describes the role of accounting information as a basis for making investment decisions but will not necessarily cause a rise in the stock price of a company, and any information that is timely provide insight to investors as a basis for making investment decisions are less able to influence rise in the stock price of a company.Keywords : closing price, ROI, relevance value and timeliness .